2023
DOI: 10.18632/aging.204570
|View full text |Cite
|
Sign up to set email alerts
|

The disturbance of thyroid-associated hormone and its receptors in brain and blood circulation existed in the early stage of mouse model of Alzheimer’s disease

Abstract: Background: Studies showed that thyroid function plays an important role in the pathology of Alzheimer’s disease (AD). However, changes in brain thyroid hormone and related receptors in the early stage of AD were rarely reported. The aim of this study was to explore the relationship between the early stage of AD and local thyroid hormone and its receptors in the brain. Methods: The animal model was established by stereotactic injection of okadaic acid (OA) into hippocampal region for the experiment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…created an early Alzheimer’s disease (AD) rat model by injecting okadaic acid (OA) into the rats’ hippocampus, which activated GSK-3, increased higher oxidative stress, generated tau hyperphosphorylation, and increased βA neurotoxicity. The study’s findings demonstrated a notable increase in FT3, FT4, TSH, and TRH levels within the brain tissues of rats in the early stages of AD, and there was a notably higher expression of TH receptors in the hippocampal tissues compared to the control group, along with FT4, TSH, and TRH were up in blood, with no change in FT3 ( 28 ). As a result, it came up that the hyperthyroid condition observed in the brain and circulation during early AD could be an early local and systemic stress repair response.…”
Section: Thyroid Dysfunction As the Results Of Admentioning
confidence: 89%
“…created an early Alzheimer’s disease (AD) rat model by injecting okadaic acid (OA) into the rats’ hippocampus, which activated GSK-3, increased higher oxidative stress, generated tau hyperphosphorylation, and increased βA neurotoxicity. The study’s findings demonstrated a notable increase in FT3, FT4, TSH, and TRH levels within the brain tissues of rats in the early stages of AD, and there was a notably higher expression of TH receptors in the hippocampal tissues compared to the control group, along with FT4, TSH, and TRH were up in blood, with no change in FT3 ( 28 ). As a result, it came up that the hyperthyroid condition observed in the brain and circulation during early AD could be an early local and systemic stress repair response.…”
Section: Thyroid Dysfunction As the Results Of Admentioning
confidence: 89%
“…Moreover TRH could be implicated in the increased excitability of hippocampal CA1 neurons [ 265 ]. On the other hand, in a model of early-stage AD induced by intrahippocampal injection of okadaic acid, which enhances the activity of the Tau kinase GSK-3β and increases Tau phosphorylation, the level of TRH increases in the brain, as does the level of TRH in the blood serum [ 266 ].…”
Section: Anorexigenic Neuropeptidesmentioning
confidence: 99%